UPAYA MANTAN PEKERJA SEKS KOMERSIAL DALAM PEMENUHAN HAK ḤAḌĀNAH PERSPEKTIF KOMPILASI HUKUM ISLAM - Handayani, Efrida (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2020)
ABSTRACT This study was examined from the background of the sense of ḥaḍānah of a former CSW at PKBM Ar-Ridho in caring for children. Some of the reasons behind the former prostitute to quit the world of prostitution include: wanting to start a better life, want a family and be the best for their children. The purpose of this research is to find out and explain the efforts of former commercial sex workers on Semanggi, Pasar Kliwon, Surakarta in fulfilling ḥaḍānah rights and to find out and explain the view of the Compilation of Islamic Law on the efforts of former commercial sex workers in fulfilling ḥaḍānah rights. This research is a type of field research with case studies using a qualitative approach. Data collection techniques carried out by observation, interviews, and documentation. Data were then analyzed using the Milles and Huberman Model which included data reduction, data display and conclusion drawing. Data on fulfilling the rights of ḥaḍānah from former commercial sex workers (CSWs) in the Ar-Ridho PKBM were analyzed from the perspective of Islamic Law Compilation. The results showed efforts to fulfill the rights of ḥaḍānah carried out by former CSWs include: the right of children in giving a good name, the right of children to receive love, the right of children to live, the right of children to obtain breast milk, the right of children to receive care, care and maintenance and the rights child in education. Fulfillment of ḥaḍānah rights of former commercial sex workers (CSWs) in the Ar-Ridho PKBM is in accordance with the Compilation of Islamic Law. Keywords: Ex-prostitute worker (PSK); Ḥaḍānah Right; Islamic Law Compilation. ABSTRAK Penelitian ini dikaji dari latar belakang sense of ḥaḍānah dari mantan PSK di PKBM Ar-Ridho dalam memelihara anak. Beberapa alasan yang melatarbelakangi mantan PSK berhenti dari dunia prostitusi antara lain: ingin memulai kehidupan yang lebih baik, ingin berkeluarga dan menjadi yang terbaik untuk anak-anaknya. Tujuan dalam penelitian ini adalah untuk mengetahui dan menjelaskan upaya mantan pekerja seks komersial Semanggi, Pasar Kliwon, Surakarta dalam pemenuhan hak ḥaḍānah serta untuk mengetahui dan menjelaskan pandangan Kompilasi Hukum Islam terhadap upaya mantan pekerja seks komersial dalam pemenuhan hak ḥaḍānah. Penelitian ini termasuk jenis penelitian lapangan dengan studi kasus menggunakan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan dokumentasi. Data kemudian dianalisis dengan Model Milles dan Huberman yang meliputi reduksi data, display data dan penarikan kesimpulan. Data-data tentang pemenuhan hak-hak ḥaḍānah dari para mantan pekerja seks komersial (PSK) di PKBM Ar-Ridho dianalisis perspektif Kompilasi Hukum Islam. Hasil penelitian menunjukan upaya pemenuhan hak ḥaḍānah yang dilakukan oleh para mantan PSK meliputi: hak anak dalam pemberian nama baik, hak anak mendapatkan kasih sayang, hak anak untuk hidup, hak anak dalam memperoleh ASI, hak anak dalam mendapatkan asuhan, perawatan dan pemeliharaan dan hak anak dalam pendidikan. Pemenuhan hak ḥaḍānah dari para mantan pekerja seks komersial (PSK) di PKBM Ar-Ridho telah sesuai dengan Kompilasi Hukum Islam. Kata Kunci: Hak Haḍānah; Kompilasi Hukum Islam; Mantan Pekerja Seks Komersial (PSK).